What does flexicurity have to gain from the capability-approach? - René Lehwess-Litzmann (Management Revue, 2012)
The policy discourse termed flexicurity is on its way of becoming a concept. Yet, this political process bears the risk of departing from the very idea of flexicurity. This paper argues that this could be prevented if flexicurity were guided by a clear conception of human well-being. The paper suggests complementing flexicurity by the capabilityapproach. Random or adverse effects of flexicurity-policy on human freedom can be avoided if 'flexibility and security' in the employment system are recognised not as ends in themselves, but as instruments at the service of people's capabilities. In principle, it is argued, flexicurity has the potential of extending human freedoms.
Keywords: B59; D63; H11; I38; J58; 650; flexicurity; capability-approach